Dogs in the dead of night - Osborne, Mary Pope.; Murdocca, Sal (2011)
Jack and Annie travel to a monastery in the Swiss Alps where, with the help of St. Bernard dogs and magic, they seek the second of four special objects necessary to break the spell on the wizard Merlin's beloved penguin, Penny.
"A Merlin mission."
"A Stepping Stone Book."
7-11
Accelerated Reader
Accelerated Reader AR
Reading Counts RC
Keywords: Magic -- Juvenile fiction; Time travel -- Juvenile fiction; Saint Bernard dog -- Juvenile fiction; Dogs -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Reading List -- 2014 Summer -- UP Elementary -- entering 2nd grade; Reading List -- 2014 Summer -- UP Elementary -- Chapter books series for summer reading; Reading List -- 2014 Summer -- Armstrong Elementary -- 1st grade; Alps, Swiss (Switzerland) -- History -- 19th century -- Juvenile fiction; Switzerland -- History -- 1789-1815 -- Juvenile fiction; Time-travel fiction; History; Juvenile works; Historical fiction; Time-travel fiction